An agent-based model for the assessment of LTV caps - Dimitrios Laliotis; Alejandro Buesa; Miha Leber; Javier Población García (European Central Bank (ECB), 2019)
We assess the effects of regulatory caps in the loan-to-value (LTV) ratio using agent-based models (ABMs). Our approach builds upon a straightforward ABM where we model the interactions of sellers, buyers and banks within a computational framework that enables the application of LTV caps. The results are first presented using simulated data and then we calibrate the probability distributions based on actual European data from the HFCS survey. The results suggest that this approach can be viewed as a useful alternative to the existing analytical frameworks for assessing the impact of macroprudential measures, mainly due to the very few assumptions the method relies upon and the ability to easily incorporate additional and more complex features related to the behavioral response of borrowers to such measures.
Keywords: D14; D31; E50; R21; 330; Borrower-based measures; macroprudential policy; house prices; HFCS survey